The Frontier Challenge Responses to the TransMississippi West - Clark, John G. (University Press of Kansas, 1971)
The story of the westward expansion of this country does not stop with the hardships encountered by travelers on the Mormon Trail, the discomforts endured by early settlers in sod houses, the bravery of the Pony Express riders, the romantic solitude of the cowboys, or the sufferings of the Indians forced to abandon their homes bleak and alien country. Much has been written about these colorful episodes and, through the courtesy of Hollywood and TV, has been brought into millions of homes in living color. But what happened to the people, including the Indians, who survived the great raid on Fort X, the bitter winters and scorching summers spent in primitive housing, the terrible loneliness and lack of communication with eastern kin? What did migrants do when they reached the end of the Mormon Trail? And did the Cherokees' Trail of tears become a neverending journey from one "relocation" to another? How did people develop and accommodate themselves to an environment which was itself constantly altered by an everchanging society?In these essays we find that tragedy and joy, victory and defeat, human fulfillment and human degradation are visible in roughly equal proportions in the story of the Americanization of the West: that the goals, both realistic and unrealistic, of one group, society, or culture are frequently pursued only at the expense of other groups; and that the skeletons in the closet of American history abound to a greater extent than a nation convinced of its own virtue is willing to admit. Racism has plagued the nation since its inception, and exploitation of one group by another was sadly a part of the Western frontier. However, there was a freshness and vigor in the history of the West. Young railroads continued to grow, linking productive farms with brawling cities. New businesses and new political parties emerged, all contributing to the growth of the region that Stephen A. Douglas called the "adhesive of the Union."This is a fascinating collection that serves to illuminate both the tragedies and accomplishments of the westward movement.